IMPLEMENTASI MEDIA INTERAKTIF KAHOOT DALAM MENINGKATKAN KETERLIBATAN SISWA DALAM PROSES PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MAN 2 KOTA SUKABUMI : Gamification Strategy Using Kahoot to Enhance Student Participation in the Learning of Islamic Cultural History at Madrasah Aliyah - Malik, Abdul; Aulia, Adinda; Zuliani, Neng Vika; Mardiyah, Siti Sayidah (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Student engagement in history education often remains low due to the dominance of conventional teaching methods that fail to meet the interactive needs of digital-native learners. This study aims to evaluate the effectiveness of the interactive media platform Kahoot in enhancing student participation in Islamic Cultural History classes. Employing a qualitative approach with a descriptive case study design, data were collected through participant observation, structured interviews, and visual documentation during classroom activities at MAN 2 Kota Sukabumi. The findings reveal that the integration of Kahoot significantly increased student engagement, demonstrated by heightened motivation, active participation in quizzes, and improved conceptual understanding. Gamification features such as point systems, time-based challenges, and peer competition created a more dynamic and enjoyable learning environment. These results reinforce the existing literature on the pedagogical potential of game-based learning, particularly in Islamic educational contexts. The study recommends the integration of interactive digital tools as an innovative instructional strategy to foster deeper engagement and improve learning quality, especially in narrative and historically rich subjects